First cosmology results using Type IA supernovae from the dark energy survey: effects of chromatic corrections to supernova photometry on measurements of cosmological parameters. Issue 4 (5th March 2019) - Lasker, J; Kessler, R; Scolnic, D; Brout, D; Burke, D L; D'Andrea, C B; Davis, T M; Hinton, S R; Kim, A G; Li, T S; Lidman, C; Macaulay, E; et al.
Abstract: Calibration uncertainties have been the leading systematic uncertainty in recent analyses using Type Ia supernovae (SNe Ia) to measure cosmological parameters. To improve the calibration, we present the application of spectral energy distribution-dependent 'chromatic corrections' to the SN light-curve photometry from the Dark Energy Survey (DES). These corrections depend on the combined atmospheric and instrumental transmission function for each exposure, and they affect photometry at the 0.01 mag (1 per cent) level, comparable to systematic uncertainties in calibration and photometry. Fitting our combined DES and low- z SN Ia sample with baryon acoustic oscillation (BAO) and cosmic microwave background (CMB) priors for the cosmological parameters Ωm (the fraction of the critical density of the universe comprised of matter) and w (the dark energy equation of state parameter), we compare those parameters before and after applying the corrections. We find the change in w and Ωm due to not including chromatic corrections is −0.002 and 0.000, respectively, for the DES-SN3YR sample with BAO and CMB priors, consistent with a larger DES-SN3YR-like simulation, which has a w -change of 0.0005 with an uncertainty of 0.008 and an Ωm change of 0.000 with an uncertainty of 0.002. However, when considering samples on individual CCDs we find large redshift-dependent biases (∼0.02 in distance modulus) for SN distances.